(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to describe the perceived stress levels among student-athletes of Universitas Negeri Makassar (UNM) in preparation for the National Student Sports Week (Pekan Olahraga Mahasiswa Nasional, POMNAS) XIX 2025. Using a quantitative descriptive design, the research employed the Indonesian-adapted version of the Perceived Stress Scale (PSS-10) to assess psychological stress one week before the national event. The participants were 75 UNM student-athletes (49 males, 26 females) representing 11 sports disciplines, including pencak silat, athletics, sepak takraw, and beach volleyball. Data were collected online through Google Forms between 1–10 September 2025 and analyzed descriptively using frequency and percentage distributions. Results showed that 17 athletes (22.7%) were categorized as having low stress, 53 athletes (70.7%) as moderate, and 5 athletes (6.7%) as high stress. The predominance of moderate perceived stress indicates that most athletes were in a psychologically adaptive and manageable state during the pre-competition phase, consistent with the Transactional Model of Stress and Coping (Lazarus & Folkman, 1984). These findings highlight the need for continuous psychological monitoring and preventive mental-skills training to maintain athletes’ readiness for competition. The study contributes to sport psychology literature by providing context-specific data using a culturally validated instrument and offers practical implications for integrating mental health support in university sports programs. The paper includes 11 references, 5 tables, and the Indonesian PSS-10 instrument as supporting material.